An insight into the communication between β-olefin/phenyl olefin-mediated acceptors and porphyrin π-system: a way to establish porphyrin based chemodosimeters and chemosensors. Issue 6 (26th January 2017) - Chahal, Mandeep K.; Sankar, Muniappan; Butcher, Ray J.
Abstract : Porphyrins bearing electron acceptors attached to β-carbon through olefin or phenyl–olefin bridges act as chemodosimeters for CN − as well as chemosensors for F −, CN − and OAc − ions depends on acceptor strength and position. Abstract : The synthesis of three new classes of mixed β-pyrrole substituted tetraphenylporphyrins, MTPP(R), MTPP(Br)2 (R) (where R = –CHC(CN)2, –CHC(CN)(COOC2 H5 ), –CH(CN)(COOH) and M = 2H, Ni(ii ), Cu(ii )) and MTPP(NO2 )(Ph- p -R′)2 (R′ = –CHO and –CHC(CN)2 and M = 2H, Ni(ii ), Cu(ii )) have been reported. The crystal structures of CuTPP(Br)2 -ECA (7a ), NiTPP(NO2 )(Ph- p -CHO)2 (9 ) and NiTPP(NO2 )(Ph- p -CH(CN)2 )2 (10 ) are highly nonplanar among β-trisubstituted porphyrins reported to date as evidenced from the mean displacement of β-pyrrole carbon (Δ C β ) in the range ±(0.39–0.674) Å. The olefin mediated ethyl cyanoacetate is in plane with the porphyrin core in CuTPP(Br)2 -ECA (the dihedral angle relative to the pyrrole NC4 -mean plane is 39.81°) while dicyanovinyl stays aside for NiTPP(NO2 )(Ph- p -CH(CN)2 )2 (dihedral angles relative to the pyrrole NC4 -mean plane are 75.03° and 67.47°). NiTPP-MN (2 ), NiTPP-ECA (3 ), NiTPP(Br)2 -MN (6 ) and NiTPP(Br)2 -ECA (7 ) act as chemodosimeters for toxic CN − ions whereas NiTPP-CAA (4 ) and NiTPP(Br)2 -CAA (8 ) act as chemosensors to detect toxic ions such as CN −, F − and OAc − depending on the acceptor strength and an obstacle in the conjugation pathway. The dicyanovinyl group in the phenyl olefinic-mediated porphyrin NiTPP(NO2 )(Ph- p -CH(CN)2 )2 (10 ) also acts as chemodosimeter for CN − ions but no vivid changes are observed via different spectroscopic methods.